Association of Cerebral Small Vessel Disease With Gait and Balance Disorders - Su, Chen; Yang, Xiaoyu; Wei, Shuqi; Zhao, Renliang (Frontiers in Aging Neuroscience, 2022)
Cerebral small vessel disease (CSVD) is a common disease in cerebrovascular diseases and an important cause of gait and balance disorders. Gait and balance disorders can further lead to an increased risk of falls and a decreased quality of life. CSVD can damage gait and balance function by affecting cognitive function or directly disrupting motor pathways, and different CSVD imaging features have different characteristics of gait and balance impairment. In this paper, the correlation between different imaging features of CSVD and gait and balance disorders has been reviewed as follows, which can provide beneficial help for standardized management of CSVD.